Початки формування армії УНР восени 1917 року - Зінкевич, Р. Д. (Видавництво Львівської політехніки, 2014)
Досліджено початки формування армії УНР та створення вищих државних військових органів 1917 року. Показано помилки Центральної Ради у військовому будівництві, які згодом призвели до низької боєздатності Армії УНР. The article is about the study of the beginnings of the Ukrainian People’s Army formation and the creation of the senior state military authorities in autumn 1917. The research shows the mistakes of the Central Council regarding the military construction, that further led to the low Ukrainian National Army fighting efficiency. There were major political changes in Russia in autumn 1917. The Bolsheviks came to power after the armed revolution. This change of the political situation had influence on the course of events in Ukraine. During this period the Central Council finished the forming of the Ukrainian national military organizational structures and the creation of the UNA bases. A characteristic feature of that period was a rapid evolution from the spontaneous methods to the emersion of the national state military policy elements, that ultimately led to the appearance of the UNR Armed Forces main body. Against anti-militarist policy of the Central Council, aimed at the elimination of the regular army and replacing it to a people’s militia, all events led to the creation of the Armed Forces as one of the state attributes. In the end of November 1917 the Ukrainian military movement reached the stage of organizational appearance, despite all mistakes in the military construction. There were senior military authorities: General Military Secretariat, that served as the National Ministry of Defence, General Staff, National Military Council and military councils on different levels of the fields. Two military districts Kyiv and Odessa also were subordinated to the Ukrainian authority. In addition, the creation of the Ukrainian Front and the appointment by the Military Secretariat for it relevant chiefs completed the process of formal submission of all parts of the former Russian army on the Ukrainian territory to the UNR government. Ukrainian military schools started training of national military personnel. Therefore, we can state that in November 1917 there was established the UNR Army. It consisted of differently typed formations. According to the ways or methods of organization they could be divided into several types: arbitrary, those that appeared spontaneously; revolutionary, whose creation often started from spontaneous revolutionary movement, and then were recognised as the official authority; planned structures – ukrainianized and newly created units, that had to become the main body of a regular national army. However, the fighting efficiency of the UNA still remained low.
Keywords: армія; Центральна Рада; Росія; більшовики; військове будівництво; army; Central Advice; Russia; bolshevists; military building